2007
DOI: 10.1016/j.mvr.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone improves structure and increases tone in the cerebral vasculature of male spontaneously hypertensive stroke-prone rats

Abstract: Background: Previous studies show that ischemic cerebral infarct size is related to cerebral vessel structure. Spironolactone, a mineralocorticoid receptor antagonist, decreases ischemic cerebral infarct size in male spontaneously hypertensive stroke-prone rats (SHRSP). Therefore, we hypothesized that chronic spironolactone treatment would improve cerebral artery structure in the SHRSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
90
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 35 publications
12
90
1
Order By: Relevance
“…With very few available options for the treatment of stroke, to reduce stroke risk it seems prudent to identify therapies aimed at primary prevention. We have shown previously that improving MCA structure reduces the damage caused by cerebral ischemia (13,41,42). In the present report, we show that chronic DOX treatment attenuates the hypertensive vascular remodeling observed in SHRSP.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…With very few available options for the treatment of stroke, to reduce stroke risk it seems prudent to identify therapies aimed at primary prevention. We have shown previously that improving MCA structure reduces the damage caused by cerebral ischemia (13,41,42). In the present report, we show that chronic DOX treatment attenuates the hypertensive vascular remodeling observed in SHRSP.…”
Section: Discussionsupporting
confidence: 75%
“…13,14,38,42). Remodeling of the resistance vasculature encompasses structural changes that lead to a reduction in the lumen diameter and an increase in the wall thickness and wall-to-lumen ratio (2,17,23,36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rigsby et al 38 and Dorrance et al 39 indicated that MR blockade by spironolactone reduced the cerebral infarction size in male stroke-prone spontaneously hypertensive rats, and MR activation with DOCA increased the size of cerebral infarcts; they suggested that MR activation results in inward hypertrophic remodeling of the cerebral vasculature and an increase in infarct size. However, cerebral aneurysms involve outward remodeling, and the vascular aneurysmal wall tends to be thin rather than thick.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Titze et al 37 showed that DOCA-salt led to a total-body sodium excess. Our and other findings suggest that MR activation increases sodium retention and that high sodium retention may have additive harmful effects on the formation of cerebral aneurysms.Rigsby et al 38 and Dorrance et al 39 indicated that MR blockade by spironolactone reduced the cerebral infarction size in male stroke-prone spontaneously hypertensive rats, and MR activation with DOCA increased the size of cerebral infarcts; they suggested that MR activation results in inward hypertrophic remodeling of the cerebral vasculature and an increase in infarct size. However, cerebral aneurysms involve outward remodeling, and the vascular aneurysmal wall tends to be thin rather than thick.…”
mentioning
confidence: 99%